PENGARUH EXPERIENTIAL MARKETING TERHADAP LOYALITAS WISATAWAN PADA PUSAT KONSERVASI TUMBUHAN KEBUN RAYA BOGOR (PKTKRB) - Wibowo, Sukarno; Purnama, Rusna (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2019)
Experiential marketing is a form of marketing that can analyze consumers by using psychological models in analyzing their behavior. The creation of consumer experience through experiential marketing is expected to develop customer loyalty. This study aims to analyze experiential marketing, tourist loyalty, as well as the influence of experiential marketing on tourist loyalty. The method used is an explanatory survey to 100 tourists visiting the Bogor Botanical Gardens, with regression analysis. Findings indicate that in general, the experiential marketing belongs to ‘very good’ category. This can be seen from the aspects of sense, feel, think, act, relate, and people; which means that by visiting an attraction, consumers gain experience in terms of feelings, thoughts, actions, as well as social relationships. Tourist loyalty to Bogor Botanical Gardens belongs to ‘fair’ category. This can be seen from the repeat purchase, retention, and referalls aspects which clearly shows that consumers can revisit and repurchase the attraction. Experiential marketing has a positive and significant influence equal to 53.3% on the tourist loyalty. This research recommends that the management of Bogor Botanical Gardens improve their experiential marketing from various aspects, including sense, feel, thought, act, relate, and people.